Glycerol-triazole conjugated rhodamine as colorimetric and fluorimetric sensor for Cu2+ - Verma, Abhishek; Gahlyan, Parveen; Bawa, Rashim; Dash, Soumya Ranjan; Prasad, Ashok K.; Kumar, Rakesh (ChemistrySelect, 2021)
{A glycerol-triazole tethered rhodamine based colorimetric and fluorimetric sensor 3 `,6 `-bis(diethylamino)-2-(((1-(1,3-dihydroxypropan-2-yl)-1H-1,2,3-triazol-4 -yl)methylene)aminospiro [isoindoline-1,9 `-xanthen]-3-one (L1) is designed and synthesized for the selective recognition of Cu2+ ion. The sensor L1 allows naked eye detection of Cu2+ ion with a fast response (<1 min). Among the various metal ions tested, the sensor L1 shows selective binding with Cu2+ through turn-on fluorescence mechanism. The sensor shows 1 : 2 binding stoichiometry with binding constant
Keywords: Cu2+ Sensor; DFT; Glycerol; Rhodamine B; Triazole

Germylene mediated reductive C-C and C-N coupling of an isocyanide and its device application - Gour, Kritika; Pramanik, Debjit; Dash, Soumya Ranjan; Shinde, Dipak Dattatray; Venugopal, Geethu; Vanka, Kumar; Rath, Arup K.; Sen, Sakya S. (Angewandte Chemie-International Edition, 2025)
We have demonstrated a unique reductive coupling of 4-iodophenyl isocyanide, facilitated by a perimidine-based N-heterocyclic germylene (NHGe), which yields a bis-spirogerma compound featuring simultaneous C-C and C-N bond formation. This reaction, which leads to the oxidation of germanium from +2 to +4, represents a significant departure from previously documented isocyanide-germylene interactions. The product exhibits extensive conjugation across its bicyclic C4Ge2N2 framework, conferring distinct photophysical properties, including prominent orange luminescence in both solution and solid states. The photophysical properties are supported by the TD-DFT calculations confirming an n ->pi* transition. The potential application of this compound in optoelectronic devices, particularly as a hole transport layer in PbS quantum dot solar cells, is also explored, with promising preliminary results.
Keywords: Germylene; hole transport layer; Isocyanide; reductive coupling